PENERAPAN ANALISIS SWOT DALAM MENINGKATKAN KINERJA KARYAWAN DI WINDOFA APPAREL - Andarias Sambo; Kunto Atmojo; Sani Mawarni; Mohammad Anno Zuhrias (Equilibrium Point : Jurnal Manajemen dan Bisnis, 2022)
Employee performance problems are closely related to the company's achievements, because employees are one of the main factors for the company in achieving the goals that have been set. The company's inability to improve the performance of its employees is an obstacle that must be faced by every company, including Windofa Apparel. This research is a qualitative descriptive study using the SWOT analysis method. Collecting data through literature and field studies with interview and observation techniques.“The results obtained are that the company's internal strengths and weaknesses are in an average internal position, while the company's external opportunities and threats are in a high external position. The position of the Windofa Apparel company is in cell II, namely in the growth strategy position which requires the company to choose a strategy that concentrates through horizontal integration. The strategy that can be used by Windofa Apparel in order to improve the performance of its employees is the SO (Strengths–Opportunities) strategy, actions that can be taken in the SO strategy include collaborating with other businesses, conducting performance development through company workshops for employees, and maximizing product promotions for both customers. new or old.Keywords: SWOT Analysis, Employee Performance